THE EFFECT OF SOCIAL PERCEPTION TRAINING ON SOCIAL COMPETENCE (SOCIAL SKILLS AND BEHAVIORAL PROBLEMS) OF EIGHTH GRADE MALE STUDENTS - Abdolreza Akbari, Gholam Hossein Maktabi, Morteza Omidian, Askar Atash Afrooz, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study was conducted to investigate the effect of social perception training on the social competence of eighth-grade male students. The research method is experimental with pre-test and post-test design with a control group. This study's statistical population was all eighth-grade male students in Dezful in the academic year 2020-21. Among them, 40 students were selected by multi-stage random sampling. Then, they were randomly divided into two experimental groups (n = 20) and a control group (n = 20) and completed the Gersham and Elliott (1990) Social Skills Questionnaire in the pre-test and post-test stages. The experimental group was examined by social perception training intervention for 10 sessions of 90 minutes, while the control group did not receive any intervention during this period. The analysis of covariance results showed that social perception training affected increasing social skills and reducing behavioral problems (p<0.001). This study results showed that generally to improve students' social competence, the use of social perception education is effective.